Sexual health knowledge, attitudes and behaviour of Sāmoan youth in Aotearoa New Zealand : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Public Policy at Massey University, Albany, New Zealand - Veukiso-Ulugia, Analosa (Massey University, 2017)
Sex and sexuality in many cultures are sensitive topics. For many Pacific communities where sex is often regarded as tapu (sacred), cultural and religious values largely frame how sexuality and pregnancy are understood. For many Sāmoans, sex is regarded as a taboo subject. While sexual activity may be a pleasurable experience, its consequences can be life-altering. In New Zealand, the sexual health status of teenagers, particularly Pacific young people, is concerning. Compared with other countries, the rates of sexually transmitted infections (STIs), unintended teenage pregnancies and suboptimal levels of contraceptive use in New Zealand are high. From a public health perspective, these issues pose serious social, economic and health risks. For teenagers, early sexual involvement and pregnancy can drastically affect their social, educational and emotional development and life chances. In an attempt to understand and address these sexual health issues, public policy agents seek appropriate information that can assist them in designing responsive interventions. This mixed methods study explores the factors that influence the sexual health knowledge, attitudes and behaviours of Sāmoan secondary school students in Aotearoa New Zealand. An analysis of information from 535 Sāmoan students that participated in the Youth ‘07 health survey was undertaken. Individual interviews with eight key informants, and eight focus groups comprised of 55 Auckland Sāmoan secondary school students were carried out. This study presents a comprehensive picture of the sexual health patterns and issues unique to Sāmoan youth living in Aotearoa New Zealand. Three broad factors - the individual, family and wider environment - influence the sexual health knowledge, attitudes and behaviours of Sāmoan youth. This study proposes that to address sexual health issues for Sāmoan communities requires an understanding of three essential concepts: ‘Context’, ‘Communication’ and ‘Co-ordination’. The significance of this research and its findings extend to a range of audiences including Sāmoan young people, families, schools, health and social service providers and policy agents.
Keywords: Teenagers; Sexual behaviour; High school students; Samoans; Research Subject Categories::SOCIAL SCIENCES::Social sciences